2021
DOI: 10.1021/jacs.1c06648
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Discovery of Multistep Chemistry Initiated by a Conical Intersection: The Challenging Case of Donor–Acceptor Stenhouse Adducts

Abstract: Detailed mechanistic understanding of multistep chemical reactions triggered by internal conversion via a conical intersection is a challenging task that emphasizes limitations in theoretical and experimental techniques. Hypothesis-driven methodologies (e.g. characterization of critical points and biased molecular dynamics) are commonly employed to explore chemical space and simulate reaction events. In this contribution, we present a discovery-based, hypothesis-free computational approach based on first princ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…The DASA switching mechanism has been elucidated by combining experimental and theoretical approaches, revealing its intermediate steps and the guidelines to design DASA photoswitches. These studies have identified different isomerization and rotation steps, followed by an electrocyclization and proton transfer mechanism that leads to the final cyclized form of the compound . Recently, insights into a three-stage single photochrome photoswitching system were obtained with a DASA derivative capable of addressing multiple molecular states .…”
Section: Introductionmentioning
confidence: 99%
“…The DASA switching mechanism has been elucidated by combining experimental and theoretical approaches, revealing its intermediate steps and the guidelines to design DASA photoswitches. These studies have identified different isomerization and rotation steps, followed by an electrocyclization and proton transfer mechanism that leads to the final cyclized form of the compound . Recently, insights into a three-stage single photochrome photoswitching system were obtained with a DASA derivative capable of addressing multiple molecular states .…”
Section: Introductionmentioning
confidence: 99%
“…[ 8–10 ] DASAs undergo a visible light‐induced, colored to colorless, open triene to closed cyclopentenone isomerization that is thermally reversible. [ 11–15 ] Their tunable absorption in the spectral range between 450 and 750 nm [ 16–21 ] enables DASA activation at wavelengths suitable for biological applications. [ 22 ] DASA‐functionalized polymers were already investigated for potential applications in a number of areas ranging from photo‐/hydrochromic, [ 23–25 ] photopatternable, [ 26–29 ] or wettability switching [ 30–34 ] surfaces and objects, to smart drug delivery, [ 35–40 ] chemical sensing, [ 41–45 ] and photoactuation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the photoswitching mechanism of DASA-based systems starts with an actinic step (E/Z photoisomerization) but is followed by a multitude of competing thermal pathways involving 4p electrocyclization, bond rotation and proton transfer. [23][24][25][26][27][28][29][30][31][32][33][34][35] In our Raucci, U and Sanchez, D. M et al -Enhanced Sampling Aided Design 3 recent work [29][30] we showed for the first time the natural evolution of the nuclear wavepacket relaxing through conical intersections via ab initio nonadiabatic and adiabatic quantum molecular dynamics (Fig. 1).…”
mentioning
confidence: 74%